My memories of India - Oaten, Edward Farley (Patna : Janaki Prakashan, 1984)
Covers the tenure of the author as a member of the Indian Educational Service, 1909-1930.
Autobiographical.
Includes index.
Keywords: Educators -- India -- Biography; Educators -- Great Britain -- Biography